THE IMPACT OF CORPORATE GOVERNANCE MECHANISMS ON THE RELATIONSHIP BETWEEN EARNINGS QUALITY AND FINANCIAL PERFORMANCE - Tammar Salih Jawad Hayder (Scholar Express Journals, 2024)
The current research aims to evaluate the impact of adopting International Financial Reporting Standards (I.F.R.S) and corporate governance mechanisms on compliance with international standards in earnings management, financial reporting preparation, and financial reporting quality (F.R.Q). An example is the 102 Country corporations listed as firms in 2014–2019, which is a sample of which is used as a measure .
Keywords: Corporate; governance; Earnings quality